Analisa Karakteristik Dielektrik dan Kimia Minyak Gas To Liquid (GTL) Sebagai Media Isolasi Transformator - Rahmat , Saepul; Ariawan, Radhi (Infotekmesin, 2022)
Gas to Liquid transformer oil with iso-paraffinic as the main constituent is an alternative insulating medium with fewer impurities, therefore its insulating strength is increasing. This study aims to determine the relationship of changes in the dielectric characteristics of transformer oil to changes in the chemical characteristics of gas to liquid oil. The object of research for gas to liquid oil is treated as the actual condition of the transformer at a temperature of 1000C, then thermal aging was carried out with temperatures of 1200C and 1500C starting from 362 hours to 1008 hours. the dielectric loss value of transformer oil still met the standard value used, namely ASTM D924 of 0.0015%, but the resistivity value was not in accordance with the standard specified by IEC 60442 which was 60 Gð®m. The value of chemical characteristics such as water content is above the ASTM D1533 standard of 35 mg/kg, the value of the acid content of the oil is above the ASTM D974 standard of 0.20 mg KOH/g, and the color scale value exceeds the predetermined limit of ASTM D1500 by 0,5.